Intraepithelial Macrophage Expressing CD163 Is a Histopathological Clue to Evaluate the Malignant Potency of Oral Lichenoid Condition: A Case Report and Immunohistochemical Investigation - Shigeoka, Manabu (Diagnostics (Basel), 2020)
Oral lichenoid conditions (OLC), including oral lichen planus (OLP), oral lichenoid lesions and oral lichenoid dysplasia, differ in pathogenesis and biological malignancy. However, distinguishing them based on clinical or histological features is difficult. It is well known that CD163(+) macrophages are associated with oral cancer aggressiveness. We recently demonstrated that CD163(+) macrophages of noncancerous lesions infiltrate the stroma, not the intraepithelial area. In this report, we describe a case of OLC that was not detected as malignant by the first local biopsy. Furthermore, we evaluated the malignant potency of OLC by retrospectively comparing the histological findings between local biopsy and resected specimens focusing on CD163(+) macrophages. A 72-year-old man with a white lesion in the unilateral buccal mucosa was diagnosed with OLP through the biopsy although invasive cancer was detected two years later. Intraepithelial CD163(+) macrophages were found not only on the resected specimen but also biopsy. This is the first report to demonstrate that intraepithelial CD163(+) macrophages may be noteworthy indicators to identify the malignant potency of OLC.